The impact of neighborhood environment on physical activity among older adults: chain mediating roles of self-efficacy and outcome expectations - Ying, Lei; Yang, Qingqing; Yu, Jizhe; Liao, Xiaoyun; Fan, Wenming (Frontiers in Aging Neuroscience, 2025)
BackgroundWith the acceleration of population aging and the increasingly prominent problem of insufficient physical activity among older adults, how to effectively promote physical activity participation among older adults has become an important issue in the field of public health. Neighborhood environment, as the primary setting for daily living among older adults, exerts considerable influence on their physical activity engagement; however, the underlying mechanisms remain inadequately understood. Grounded in Social Cognitive Theory, this study aimed to examine the impact of neighborhood environment on physical activity among older adults and to test the chain mediating effects of self-efficacy and outcome expectations.MethodsThis study employed a cross-sectional design to collect data on physical activity participation from 937 older adults residing in 12 communities across Chengdu, Sichuan Province, China, through questionnaire surveys. Assessment instruments included the Neighborhood Environment Scale, International Physical Activity Questionnaire, Self-Efficacy Scale, and Physical Activity Outcome Expectations Scale to comprehensively evaluate participants’ environmental perceptions, physical activity levels, and psychological cognitive characteristics. Following data collection, statistical analyses were conducted using SPSS 26.0, with structural equation modeling (AMOS) and Bootstrap methods employed to test potential mediating effects and ensure the reliability of results.ResultsThe analyses revealed significant positive correlations among neighborhood environment, physical activity, self-efficacy, and outcome expectations. Specifically, neighborhood environment demonstrated a significant direct effect on physical activity among older adults, indicating that favorable neighborhood environments directly facilitate physical activity participation. Furthermore, self-efficacy and outcome expectations exhibited a chain mediating effect between neighborhood environment and physical activity, whereby neighborhood environment indirectly influenced physical activity levels through enhancing individual exercise self-efficacy and outcome expectations.ConclusionThis study elucidates the underlying mechanisms between neighborhood environment and physical activity among older adults, Neighborhood environment is not only directly associated with physical activity levels among older adults but also indirectly influences physical activity through two psychological cognitive mediators: self-efficacy and outcome expectations.